2001
DOI: 10.1139/h01-013
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Fitness and Health

Abstract: The purpose is to examine the relationship between musculoskeletal fitness and health status. Muscular strength is positively associated with independence and overall quality of life, and negatively associated with morbidity and potentially premature mortality. Muscular endurance is positively related to overall quality of life. Elevated muscular endurance may reduce the incidence of falling and its associated injuries. Muscular power is predictive of functional capacity, resultant disability, and potentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0
20

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(129 citation statements)
references
References 28 publications
3
106
0
20
Order By: Relevance
“…Interventions that improve musculoskeletal fitness appear to be particularly important for improving the health status of frail elderly people (who have a low musculoskeletal reserve). 9,10 This research has revealed clearly the importance of engaging in activities that tax the musculoskeletal system and is supported by findings from a recent epidemiologic investigation. 104 This evidence provides direct support for the recent recommendation that resistance training and flexibility exercises be performed at least twice a week to maintain functional status, promote lifelong physical activity and enhance overall quality of life.…”
supporting
confidence: 61%
See 3 more Smart Citations
“…Interventions that improve musculoskeletal fitness appear to be particularly important for improving the health status of frail elderly people (who have a low musculoskeletal reserve). 9,10 This research has revealed clearly the importance of engaging in activities that tax the musculoskeletal system and is supported by findings from a recent epidemiologic investigation. 104 This evidence provides direct support for the recent recommendation that resistance training and flexibility exercises be performed at least twice a week to maintain functional status, promote lifelong physical activity and enhance overall quality of life.…”
supporting
confidence: 61%
“…9,10,[45][46][47][48] In a large prospective study, 46 each increase of 500 kcal (2100 kJ) in energy expenditure per week was associated with a decreased incidence of type 2 diabetes of 6% (relative risk 0.94, 95% CI -0.90 to 0.98)). This benefit was particularly evident among people at high risk of diabetes (i.e., those with a high body mass index), a finding that has been supported by several other investigators.…”
Section: Diabetes Mellitus Primary Preventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Development in strength and muscle mass volume is of clinical interest since this can reduce risks of falling accidents and increase the ability to handle daily activities [25].…”
Section: Introductionmentioning
confidence: 99%